Effect of Mixing Variables on Physical Properties of Modified Bitumen Using Natural Rubber Latex - E., Shaffie; A. K., Arshad; A., Alisibramulis; J., Ahmad; W., Hashim; Z., Abd Rahman; Putra Jaya, Ramadhansyah (IAEME Publication, 2018)
Modification of bitumen using polymers has been used from a long time to solve the roads problem which subjected to several distresses; mostly due to heavy traffic, poor bitumen properties, climatic condition and improper mix design. The application of natural rubber latex (NRL) in asphalt mixtures is intended to improve the physical characteristic of the bitumen. However, the properties of NRL bitumen in hot mix asphalt (HMA) pavement are still unclear due to influence of mixing variables factors of NRL with bitumen. This paper presents the procedure for determining the physical properties of bitumen as a function of various mixing variables (temperature, time and speed) using 80/100 penetration grade bitumen with different percentages of NRL. The bitumen was modified with 2, 4, 6, 8 and 10% by weight of bitumen in order to determine the appropriate proportion of NRL that can achieve the specifications required through penetration, softening point, viscosity and penetration index testing. The results of this investigation indicated that the mixing variable; temperature, time and speed for the NRL bitumen have significant effect on the bitumen properties and 8% by weight of bitumen is the most effective proportion that having potential to improve physical properties of bitumen such as increasing softening point and decreasing the penetration and also increase the penetration index. Therefore, it can be concluded that the NRL polymer is suitable to be used as a modifier to modified bitumen in order to enhance the properties of the bitumen and thus improves the physical properties of bitumen.